IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DI SEKOLAH PENGGERAK - Seni Asiati; Uswatun Hasanah (Jurnal Lingkar Mutu Pendidikan, 2022)
The Merdeka Curriculum has a difference compared to the 2013 Curriculum, namely that there is a Pancasila Student Profile Strengthening Project. This project supported of intracurricular activities whose ultimate goal is not only to increase competence but to build and improve the character of students as Pancasila Student Profiles through projects that raise issues or problems in the surrounding environment. Currently, the Pancasila Student Profile Strengthening Project has been required to be implemented by Driving School. By 2021 there are 54 Driving Schools that should have implemented the project. Therefore, this study wanted to see to what extent the stages of implementation of the Pancasila Student Profile Strengthening Project at the Driving School,the obstacles that hindered project implementation and provided solutions to project implementation problems by means of surveys through instruments. Keywords: Implementation, Pancasila Student Profile Strengthening Project, Driving School.